Strategic Approaches to University Product Marketing in the Global Market - Vivi Silvia; Naswatun Zikra; Zia Thahira; Taufiq C. Dawood; Nazamuddin Nazamuddin; T. Zulham; Apridar Apridar; Aliasuddin; Srinita Srinita; Chenny Seftarita (International Journal Of Community Service, 2024)
This community service program, conducted by Universitas Syiah Kuala (USK) in collaboration with Thaksin University (TSU), aimed to promote effective marketing strategies for university best local products to expand their presence in global markets. The program focused on the utilization of Aceh's patchouli oil, a product with substantial international demand, as an example of how local resources can be developed into competitive products for the global market. The methods used included dissemination sessions, interactive discussions, and demonstrations of products produced by the cooperative to both local farmers and academic partners in Thailand. The results indicated increased participant awareness of the potential of local products, with the Inovac ARC Cooperative playing a key role in the development and marketing of these products. The success of the program was attributed to the integration of product innovation, strategic marketing, and collaboration with international partners. Future programs should focus on strengthening international partnerships and exploring digital marketing strategies to enhance market access for local products. Decision-makers are encouraged to support cooperative initiatives that combine local expertise with global market standards.